American politics & government today - Bianco, William T.; Canon, David T.; Owens, Kimberly A.; Wehrli, James; Strong, Julie U. (W.W. Norton & Company, 2022)
"American Politics and Government Today teaches students exactly what they need to know to succeed in the course and become informed citizens. The part structure and chapter organization clearly maps to the five AP® U.S. Government and Politics units, for close alignment with the course framework. In each chapter, integrated policy coverage allows students to see how social, economic, or foreign policy relates to real-life situations, while AP®-style multiple-choice questions and the full range of free response questions offer students practice opportunities at the end of each chapter"--